Properties of Cu-xFe(3)O(4) Nanocomposites for Electrical Application - Predescu, Andra Mihaela (Materials (Basel), 2020)
Copper matrix nanocomposites reinforced with magnetite nanoparticles were developed using powder metallurgy. Various processing parameters were taken into consideration, such as magnetite content, compaction pressure, sintering time and temperature. The nanopowder blends were compacted using various uniaxial pressures and sintered at 650 and 800 °C in order to study the influence of processing parameters on morphology, structure, thermal, magnetic and mechanical properties. The structure and morphology of the nanocomposites analyzed by X-ray diffraction (XRD), bright field transmission electron microscopy (TEMBF) and scanning electron microscopy (SEM) showed that sintered composites retained the nanoscale characteristics of the initial Fe(3)O(4) and Cu nanopowders. These nanocomposites have good cold-rolling deformability and Vickers micro-hardness. The Cu-xFe(3)O(4) nanocomposites have thermal and magnetic properties that make them suitable for electronical applications.